The Little Data Book on Gender 2016 - World Bank (Washington, DC: World Bank, 2015)
This handy pocket guide is a quick reference for users interested in gender statistics. The book presents gender-disaggregated data for more than 200 economies in an easy country-by-country reference on demography, education, health, labor force, political participation and the Millennium Development Goals. The book’s summary pages cover regional and income group aggregates